A Semiotics Analysis Found on Music Video of You Belong with Me by Taylor Swift - Nita Sukma Fitria (CV. Tirta Pustaka Press, 2023)
This research entitles “A Semiotics Analysis Found on Music Vidio of You Belong with Me”.The aim of this research was to investigate and analyze the verbal and visual signs and the meaning itself in the music video of “You Belong with Me” by Taylor Swift. The type of this research was qualitative research. In collecting data, the writer used the method of observation and documentation by classifying videos into pictures in the form of sequences.The results of this study indicate that the semiotic signs contained in this music video are in the form of visual displays contained in body language in the music video which tells about a male friend that Swift likes who actually has a lover, and verbal signs contained in the music video is a paper that contains writing that is used to communicate. Based on the result of the analysis,it can be concluded as there are two classifications,namely: verbal sign and visual sign. In verbal sign, it was found eight data. In visual sign, it was found seven data. The concept of music video of You Belong With Me describe someone who is in love with someone where that person has been with a lover who doesn't appreciate it at all. In the data found, verbal and visual sign explained about caring, disappointment, jealousy, and express feelings.